A Study of Vitamin D and Calcium Level in Beta Thalassemia Major in Duhok Province - Ghorbat Saleh Ali; Malika Kassem Najeeb; Amad M. Saleh Jubrail; Zeliha Selamoğlu (Turkish Journal of Agriculture: Food Science and Technology)
β-thalassemia major is severe hemolytic anemia which requires repeated blood transfusion and for survival, which leading to iron overload. Serious complications due to iron over load are recognized in the thalassemia patients. objectives Vitamin D and calcium are important factors for homeostasis of calcium in this study. This study was conducted for a period of two year including from patients with β- thalassemia major from Duhok Thalassemia Centre between 2014 -2015. Thirty eighth β- thalassemia major patients and thirty eighth persons with age- matched as control group were enrolled in the study. Serum concentration of 25- hydroxy vitamin D and calcium were estimated by enzyme linked fluorescent assay and colorimetric method, respectively. In patients, the level of serum 25- hydroxy vitamin D was significantly lower 11.11±4.36 ng/mL compared with control group (14.03±5.96ng/mL). Vitamin D deficiency is observed about 94.73% in patients. The mean level of serum calcium in patients group is 7.9±0.47mg/dL and 8.98±0.77 mg/dL in control group. There was a statistically significant difference in serum calcium value between patients and control group. 44.73% of patients have hypocalcaemia. This study demonstrated a high prevalence of Vitamin D deficiency and low total serum calcium levels in thalassemia patients with a significantly lower than healthy group. Hypocalcemia and vitamin D deficiency may be results from the negative effect of the repeated blood transfusion and malnourishment.